2014
DOI: 10.1161/strokeaha.113.004009
|View full text |Cite
|
Sign up to set email alerts
|

Warfarin Versus Aspirin for Prevention of Cognitive Decline in Atrial Fibrillation

Abstract: Therefore, it can be inferred that anticoagulation reduces risk of cognitive decline in AF by preventing overt strokes. What is not known is whether anticoagulation reduces the risk of cognitive decline in AF through any other mechanism, such as by reducing the risk of silent stroke. The aim of this analysis is to compare the efficacy of warfarin with aspirin for prevention of cognitive decline in a primary care population of Background and Purpose-Atrial fibrillation is associated with decline of cognitive fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…This may be recognised as a practical contribution of our study. Cognitive impairment and silent brain injury may also be suggested as a guide for prescribing anticoagulation treatment for patients at low risk of AF to prevent cognitive decline [11,17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be recognised as a practical contribution of our study. Cognitive impairment and silent brain injury may also be suggested as a guide for prescribing anticoagulation treatment for patients at low risk of AF to prevent cognitive decline [11,17].…”
Section: Discussionmentioning
confidence: 99%
“…The following pathomechanisms of the relationships between AF and cognitive impairment have been suggested: (a) stroke due to embolus of a cerebral artery; (b) asymptomatic cerebral artery microembolism with mate-rial of cardiac origin, e.g. due to insufficient anticoagulation; (c) haemodynamic complications of atrial arrhythmia leading to a decrease in cerebral blood flow; (d) anticoagulation complications with haemorrhagic stroke; (e) systolic or diastolic cardiac failure; and (f) the effect of characteristics and comorbidities leading to heart and vascular injury, such as: increased age, gender, hypertension, diabetes mellitus, hyperlipidaemia, obesity, low physical activity, and systemic inflammatory status [10,[13][14][15][16][17][18]. Relationships between N-terminal pro-B-type natriuretic peptide (NT-proBNP) and left atrium dilatation are also reported [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…(Figure 1) Of these, 19 studies (n=15,876 participants) were suitable for inclusion [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] (five were extended abstracts, supplemented, where possible, by additional data from authors [23][24][25][26][27]). (Table 1) The internal validity of title searching process was confirmed as no titles from focused review were missed in the full review.…”
Section: Resultsmentioning
confidence: 99%
“…(Table 1) Of five RCTs identified, only one had cognitive data suited to our proposed analysis. [11] In this study, the Birmingham Atrial Fibrillation Treatment of the Aged (BAFTA) study, older adults were randomised to warfarin (target International Events (ACTIVE-W) study reported association between time in therapeutic range and cognitive scores but did not provide cognitive scores by treatment arm. [13] Similarly, a single-centre study of warfarin versus aspirin provided only aggregate cognitive data.…”
Section: Resultsmentioning
confidence: 99%
“…Atrial fibrillation is independently associated with cognitive dysfunction, with increased thrombin generation and fibrin turnover, with higher D-dimer, prothrombin fragment 1+2 and thrombin-anti-thrombin comlexes were reported in patients with dementia and FA when compared with patients with only FA [30]. However, it has been reported that anticoagulation was no better than aspirin in protecting against cognitive decline as measured by the mini-mental score, other than that provided by preventing clinical stroke [31]. However, with proper instruction to the patient or carer, mild to moderate cognitive dysfunction does not delay the time required to achieve therapeutic anticoagulation nor decreased anticoagulation stability in terms of number of clinic visits compared with patients with normal cognitive function [32].…”
Section: Introductionmentioning
confidence: 99%